Effects of taurine supplementation in live feeds on larval rearing performance of California yellowtail Seriola lalandi and white seabass Atractoscion nobilis. (26th February 2016) - Rotman, Federico; Stuart, Kevin; Drawbridge, Mark
Abstract: The larval rearing performance of California yellowtail ( Seriola lalandi ) and white seabass ( Atractoscion nobilis ) was compared between larvae fed taurine‐supplemented rotifers ( Brachionus plicatilis ) and Artemia ( Artemia franciscana ) and control groups fed live feeds with no taurine enhancement. Results from the S. lalandi trial demonstrated that when fed taurine‐supplemented rotifers, survival was significantly higher than the control group (20.1% vs. 9.1%, P  < 0.01) as was notochord length (5.43 mm vs. 5.13 mm, P  < 0.005). No larval performance differences were detected between experimental and control treatments of A. nobilis . Biochemical analyses demonstrated that taurine concentrations were significantly elevated in both S. lalandi (23.7 vs. 2.7 mg g −1, P  < 0.001) and A. nobilis (33.0 vs. 21.0 mg g −1, P  < 0.005) when live feeds were supplemented with taurine. Results suggest that taurine is a limiting nutrient in the larviculture of S. lalandi but may not be for A. nobilis .